Psychosocial impact of climatotherapy in young patients with psoriasis: a 3-month cohort study - Nordgren, Max; Duvetorp, Albert (Frontiers in Medicine, 2024)
Ultraviolet rays are known to have positive effect on psoriasis but the cold climate and latitude in Northern Europe reduces access to sun. Climatotherapy is a treatment modality where the patient is relocated to a warmer region with high UV-index. Young patients with psoriasis can be particularly burdened by the disease and studies have shown an association between psoriasis and mood disorders. Patients who have undergone climatotherapy often report beneficial psychological effects after treatment, but this has not yet been studied. To explore the psychosocial impact of climatotherapy, an observational study was designed. 34 participants (median age 24) underwent three weeks of treatment in Gran Canaria (Spain) and responded to questionnaires assessing psychosocial aspects of disease. Climatotherapy was associated with significant reduced scores of HADS, PSS-10, PSQ, EQ VAS, DLQI and itch intensity at end of, and at 3 months after end of treatment compared to before treatment onset. The results suggest that climatotherapy not only exerts effects on psoriasis skin disease but also improve symptoms of anxiety, depression, perceived stigmatization, stress, quality of life, self-assessed overall health perception and itch intensity. The results can be of use in the decision-making process when choosing a suitable treatment for young patients with psoriasis.